ADP‐ribose transferase PARP16 mediated‐unfolded protein response contributes to neuronal cell damage in cerebral ischemia/reperfusion. Issue 2 (24th January 2023) - Wang, Jinghuan; Xu, Jie; Dong, Yejun; Su, Zhenghua; Su, Haibi; Cheng, Qianwen; Liu, Xinhua
Abstract: Ischemic stroke is known to cause the accumulation of misfolded proteins and loss of calcium homeostasis, leading to impairment of endoplasmic reticulum (ER) function and activating the unfolded protein response (UPR). PARP16 is an active (ADP‐ribosyl)transferase known tail‐anchored ER transmembrane protein with a cytosolic catalytic domain. Here, we find PARP16 is highly expressed in ischemic cerebral hemisphere and oxygen–glucose deprivation/reoxygenation (OGD/R)‐treated immortalized hippocampal neuronal cell HT22. Using an adeno‐associated virus‐mediated PARP16 knockdown approach in mice, we find PARP16 knockdown decreases infarct demarcations and has a better neurological outcome after ischemic stroke. Our data indicate PARP16 knockdown decreases ER stress and neuronal death caused by OGD/R, whereas PARP16 overexpression promotes ER stress‐mediated cell damage in primary cortical neurons. Furthermore, PARP16 functions mechanistically as ADP‐ribosyltransferase to modulate the level of ADP‐ribosylation of the corresponding PERK and IRE1α arm of the UPR, and such modifications mediate activation of PERK and IRE1α. Indeed, pharmacological stimulation of the UPR using Brefeldin A partly counteracts PARP16 knockdown‐mediated neuronal protection upon OGD/R treatment. In conclusion, PARP16 plays a crucial role in post‐ischemic UPR and PARP16 knockdown alleviates brain injury after ischemic stroke. This study demonstrates the potential of the PARP16‐PERK/IRE1α axis as a target for neuronal survival in ischemic stroke. Abstract : In response to ischemia injury, PARP16 is increased and modulates the level of ADP‐ribosylation of the corresponding PERK and IRE1α, leading to activating PERK and IRE1α during the UPR, which at least partly contributes to ER stress‐mediated neuronal damage.